Quality improvement for manufacturing process by using 7 QC tools in SME - Muhammad Hamizan, Khalid (2013)
The aim of this project is studying the quality improvement after implementation of 7 QC tools in a manufacturing process in selected Small Medium Enterprise (SME) company. It is to detect the defects that occurred in the manufacturing process and analyzed using 7 QC tools. Besides that, the new design has been proposed for defect reduction and improving the production line. The chosen company was Kilang Keropok MakTeh and product that being analyzed is keropok sira. The main scope of this project is the implementation of 7 QC tools. Observation throughout the production line is done. There are ten main processes which are mincing, mixing, shaping, boiling, drying, freezing, slicing, frying, flavouring, and packaging. By using a check sheet, defects that occur throughout the production line are collected in 30 days. The data are then arranged back using Pareto Chart according to the frequency of the defects. The data are arranged from the highest defect to the lowest defect. The highest defect detected was under cook problem. Brainstorming session is done with the workers and also the manager to create the cause and effect diagram to details the problem. All possible causes are categorise under 4M which are Manpower, Machines, Materials, and Methods. Based on the cause and effect diagram, the improvement is generated. The improvement is to fabricate separators inside the boiler. Current boiler has problems such as low heating temperature and uneven temperature. Referring to Heat Transfer theory, small area needs only need small value of heat to raise the temperature to the desire temperature. Reducing the area of heating inside the boiler by inserting the separators, temperature inside the boiler is increased and the temperature became more stable. All data is tabulated in form of graphs and tables. Percentage of defects reduce is also calculated.